A Major Decision to Deeply Understand the Path of Peaceful Development - Qi, Youqiang; Zeng, Xin; Li, Linqi (Journal of Education and Educational Technologies, 2023)
We should deeply understand the important choice of the "Thucydides Trap", analyze the strategic measures that conform to the development trend of the times, accurately understand the essence of the path of peaceful development, adhere to the bottom line thinking principle, break the historical curse of national power and hegemony, and improve the convergence of interests of all countries. The goal is to build a "Community of Common Destiny" as the entity direction, the concept is to build a "world harmony" as the cultural basis, and the method is to adhere to "win-win cooperation" as the main focus.